Exploring through the digital edge: application of present-day tactics in modernized marketing digitally by CSR Axis Limited - Ahmed, Ehsan (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.